Recent advances bioactive 1,2,4-triazole-3-thiones - SÜZGÜN, PELİN; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2015)
Triazoles are heterocyclic compounds which have a five-membered ring of two carbon atoms and three nitrogen atoms. These structures have been interest in the development of novel compounds with anticonvulsant, antidepressant, antioxidant, anti-inflammatory, analgesic, antinociceptive, antibacterial, antimycobacterial, antifungal, antiviral, anticancer, anti-parasitic, anti-urease and other activities. Therefore, many researchers have synthesized these compounds as target structures and evaluated their biological activities. This review contains various pharmacological activities of 1,2,4-triazole-3-thiones in one place and it is also the milestone for the new research towards this moiety. (C) 2014 Elsevier Masson SAS. All rights reserved.
Keywords: 1,2,4-Triazole-3-thione; Ribavirin; Fluconazole; Anastrozole; Etodolac 1,2,4-triazole; Diflunisal 1,2,4-triazole; CLASSICAL ANTIEPILEPTIC DRUGS; INDUCED SEIZURE MODEL; ANTIMICROBIAL ACTIVITIES; MANNICH-BASES; 1,3,4-THIADIAZOLE DERIVATIVES; BIOLOGICAL EVALUATION; UREASE INHIBITION; ANTIINFLAMMATORY ACTIVITIES; ANTICONVULSANT ACTIVITY; ANTIBACTERIAL ACTIVITY